Designing and manufacturing bottled drinking water treatment system with capacity 07 m3/day by ion exchange fiter and plasma technology - Trần Ngọc Đảm; Lê Mạnh Hùng (Journal of Technical Education Science, 2015)
Nowadays, because of the convenience, bottled drinking water is becoming very popular. However, there have been a lot of disadvantages in dealing with bottled drinking water by using traditional technology such as using chemical (chlorine) treatment, the reverse osmosis technology (RO) or nanofiltration technology… that are system complexity, occupying a large area, low efficiency, no health insurance (filtered out needed mineral for the body),… In this study, the bottled drinking water treatment system using carbon filtering, ion exchange and plasma technology at low temperature and at atmostpheric pressure was designed and developed to solve the above disadvantages. The physical, chemical, and microbial indicators in treated tap water were tested in Quality Assurance and Testing Center 3 (QUATEST 3), Pasteur Institute of Ho Chi Minh City and Dong Nai province’s Preventive Medicine Center all satisfied QCVN 6-1:2010/BYT standard. The effects of voltage, current and time to processing performance were examined and evaluated. With input flow rate 0.7l/min/module, voltage 20 kV, current 2A, the bacteria were killed completely.